Effects of hops β-acid extract (Humulus lupulus L.) on cattle performance and fermentation by ruminal microbes - Axman, Justin (Kansas State University, 2015)
Hops β-acid extract was fed to 80 heifers (389 ± 23.6 kg initial BW) to assess impact on feedlot performance and ruminal fermentation. Heifers were randomly assigned to individual pens and fed once daily for 147 d. Treatments were a control (no additive); 33 mg monensin (Elanco Animal Health, Greenfield, IN)/kg diet DM; and 10, 25, 50 mg β-acid extract of hops (DSM Nutritional Products, France)/kg diet DM. Ruminal fluid was collected on d 44 and 86 by rumenocentesis for analyses of VFA, lactate, and NH[subscript]3 concentrations. Cattle were harvested at a commercial abattoir on d 147. Hops β-acids decreased propionate (P = 0.01) concentrations and increased caproate (P = 0.05), A:P (P = 0.04), and ammonia concentrations (P = 0.03) compared to monensin. Growth performance of heifers fed β-acid or monensin was not different than that of heifers fed the control diet. Additionally, two in vitro studies were conducted to evaluate effects of hops β-acid extract on starch fermentation by mixed microbial populations from the bovine rumen. In trial 1, 2 treatments were assigned in triplicate to fermentation bottle, fitted with Ankom[superscript]RF1 Gas Production System modules (Ankom[superscript]RF Technology, Macedon, NY) using starch as substrate (Difco Soluble Starch; Dickinson and Company, Sparks, MD) and either 0 or 33 mg hops β-acid extract (10.99% active hops beadlet; DSM Nutritional Products, France)/kg substrate. Gas production was measured over 30 h. Terminal pH, IVDMD, and VFA and lactate were measured after 30 h of fermentation. Gas production increased in response to β-acid (P ≤ 0.05). Terminal pH, IVDMD, VFA, and lactate were unaffected by addition of β-acid extract (P ≤ 0.05). In trial 2, pH, VFA concentrations, and IVDMD were measured at 6-h intervals during a 30-h incubation period using 36 fermentation tubes. There was no effect of hops β-acid on in vitro fermentation (P > 0.05). In conclusion, under the conditions of these experiments, hops β- acid extracts hops had little impact on feedlot performance, though there are indications of an impact on ruminal fermentation.
Keywords: Beta-acid; Hops; Feedlot; In vitro; Cattle; Animal Sciences (0475)